Unilateral Left-Sided Tessier Type 4 Facial Cleft in a 6-Mont-Old Infant: A Case Report with Surgical Reconstruction and Outcome - Rizka Fakhriani; Fadli Robby Amsriza (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Cleft Tessier is the most complex classification characterized by oro-orbital malformations with a transverse defect in the mouth extending to the nose and crossing to the lower eyelids. Recent research shows a lack of optimal reconstruction techniques, both surgical methodology and procedural. This case report aims to describe the clinical presentation, surgical reconstruction methodology, and outcomes in a 6-month-old baby with a left unilateral Tessier type 4 facial cleft. Subject and Methods: A 6-month-old female newborn appears with a congenital left unilateral facial cleft that has existed since birth. Ocular examination showed partial involvement of the lower eyelid with a risk of exposure, while the eyeball was intact. Tessier type 4 cleft arises from failure of fusion between the maxillary and lateral nasal prominences during embryogenesis. Results: Surgical management focuses on restoring both function particularly ocular protection and oral competence and facial aesthetics. Early intervention during infancy offers advantages such as improved tissue healing, better adaptation to facial growth, and reduced psychosocial impact. The reconstruction results achieved good initial functional and esthetic outcomes. Further monitoring during the growth period is necessary to assess facial asymmetry and hyperpigmentation that may occur. Conclusion: Infant reconstruction can yield better esthetics and function, although monitoring and follow-up actions are necessary.